The ADB's story - Fernon, Christine; Nolan, Melanie (ANU E Press, 2013)
'The Australian Dictionary of Biography captures the life and times and culture of this country in an absolutely distinctive and irreplaceable way. It is the indispensable record of who we are, and of the characters who have made us what we are. I could not be prouder of ANU's continuing role as custodian of this crucial part of our national legacy.' Professor the Hon. Gareth Evans AC QC, Chancellor, The Australian National University 'A mature nation needs a literary pantheon of inspiring and instructive life histories, a gallery of all the possibilities of being Australian. The Australian Dictionary of Biography responds to that vital need in our culture.
Keywords: Australiens; Biography; Encyclopedias and dictionaries; History: specific events and topics; History; HISTORY; Humanities; Social and cultural history; Biography -- Dictionaries -- History; Encyclopedias and dictionaries -- Australia -- History; Australian history; Australian dictionary of biography / History; Australia / Biography / Dictionaries; Australia / Biography / History and criticism; Australie / Biographies / Dictionnaires anglais; Australie / Biographies / Histoire et critique; Australia; Electronic books; Biographies; Criticism, interpretation, etc; Dictionaries